2019
DOI: 10.1155/2019/3494937
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D as a Principal Factor in Mediating Rheumatoid Arthritis-Derived Immune Response

Abstract: Rheumatoid arthritis (RA) is a systemic multifactorial autoimmune disorder. The interactions between diverse environmental and genetic factors lead to the onset of this complex autoimmune disorder. Serum levels of vitamin D (VD) are involved in the regulation of various immune responses. Vitamin D is a key signaling molecule in the human body that maintains calcium as well as phosphate homeostasis. It also regulates the functions of the immune system and, thus, can play a substantial role in the etiology of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 154 publications
2
41
0
2
Order By: Relevance
“…Elderly adults are at risk for VD deficiency due to several factors, including decreased pre-VD production, poor skin integrity decreased dietary intake of VD, increasing adiposity, obesity, decreased renal function, as well as less time spent outdoors [120]. VD deficiency has been linked to various aging-related inflammatory diseases, including rheumatoid arthritis, asthma, inflammatory bowel disease, multiple sclerosis, cardiovascular disease, hypertension, diabetes mellitus, and cancer [121]. Additionally, there is a correlation between VD deficiency and risk of respiratory tract infection such as COVID-19 [122].…”
Section: Aging and Vitamin D Deficiencymentioning
confidence: 99%
“…Elderly adults are at risk for VD deficiency due to several factors, including decreased pre-VD production, poor skin integrity decreased dietary intake of VD, increasing adiposity, obesity, decreased renal function, as well as less time spent outdoors [120]. VD deficiency has been linked to various aging-related inflammatory diseases, including rheumatoid arthritis, asthma, inflammatory bowel disease, multiple sclerosis, cardiovascular disease, hypertension, diabetes mellitus, and cancer [121]. Additionally, there is a correlation between VD deficiency and risk of respiratory tract infection such as COVID-19 [122].…”
Section: Aging and Vitamin D Deficiencymentioning
confidence: 99%
“…In this autoimmune disease using calcitriol supplementation reduces serum levels of antibodies and slows the progression of β cell destruction down in the early stages of the disease [38], Interestingly, it has also been demonstrated that in Systemic Sclerosis (SSc) [39] the VDR could act as a negative regulator of TGF-β/ Hydroxyproline, col1a1, col3a1 and alfa-SMA mRNAs ↓ Prevention of bleomycin-induced lung fibrosis in a murine model [48] Smad signaling, thus making vitamin D a putative antifibrotic treatment in the early stages of the disease. Although the immunoregulatory function of activated vitamin D has been widely demonstrated, its role in modulating disease activity in patients with autoimmune diseases, such as rheumatoid arthritis was only recently showed [40,41]. In a German study on a selected cohort of patients with juvenile idiopathic arthritis (JIA), vitamin D levels not only proved to be lower than those of their peers from the general population, but were also found to be inversely correlated with disease activity and the risk of progression to an extended disease course and/or JIA-associated anterior uveitis [42].…”
Section: Vitamin D In Autoimmune Diseasesmentioning
confidence: 99%
“…Additionally, vitamin D can modulate both adaptive and innate immunity [ 191 ]. Indeed, vitamin D deficiency is associated with several autoimmune diseases [ 192 ], for example, rheumatoid arthritis (RA) [ 193 , 194 ], inflammatory bowel disease (IBD) [ 195 , 196 , 197 , 198 ] and multiple sclerosis (MS) [ 199 , 200 , 201 , 202 ]. Associations between low vitamin D status and autoimmune thyroid diseases and thyroid cancer were also found [ 203 ].…”
Section: Vitamin D: State Of the Artmentioning
confidence: 99%